Effect of defaunation of rumen functions in buffaloes fed high concentrate diet - NANGIA, O P; SHARMA, RITA (The Indian Journal of Animal Sciences, 2013)
An experiment was conducted to study rumen functions in the presence or absence of rumen protozoa in buffaloes maintained on high concentrate diet. The animals were defaunated by intra-ruminal infusion of sodium dioctyl sulpho-succinate. Rumen pH and total volatile fatty acids concentration in rumen did not differ significantly as a result of defaunation. whereas the molar proportion of propion ate increased and thatof acetate and butyrte decreased. Defaunated animals had significantly higher cellulose digestion, higher total bacterial count and microbial protein nitrogen, whereas total ruminalnitrogcn ano nitrogen concentrationsdecreased significantly.